Lacertopontonia chadi gen. et sp. nov., a new oyster-associated Pontonia-like pontoniine shrimp (Crustacea, Decapoda, Palaemonidae) from the Great Barrier Reef of Australia - Marin, Ivan (Zootaxa, 2011)
A new genus and species of pontoniine shrimp, Lacertopontonia chadi gen. et sp. nov., associated with cockscomb oyster Lopha cristagalli (Linnaeus, 1758) (Bivalvia, Ostreidae) is described from Lizard Island, the Great Barrier Reef, Queensland, Australia. The new genus is presently monotypic and can be distinguished from all known Indo-West Pacific bivalve-associated pontoniine shrimps by smooth body, the absence of antennal and hepatic teeth on carapace, the presence of three pairs of dorsal submarginal spines on telson and only two pairs of posterior telson spines, short and robust equal pereiopods II, simple dactyli of ambulatory pereiopods and short uropodal exopod without movable spine at its distolateral angle.